2018
DOI: 10.1111/jsap.12808
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella serotypes isolated in geckos kept in seven collections in southern Italy

Abstract: Salmonella spp. can be isolated from apparently healthy captive gecko which should be considered as a potential source of infection for humans and other companion animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 20 publications
(49 reference statements)
1
10
1
Order By: Relevance
“…AMP was the third most frequent resistance shown in this study of Salmonella reptile strains, in line with a previous study conducted on species of gecko in Italy (10). This antibiotic is the most widely used in human medicine in Spain (76) and could thus be implicated in possible transmission of resistance from humans to reptiles, as a consequence of the direct and indirect contact between reptiles and their owners (75,77,78).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…AMP was the third most frequent resistance shown in this study of Salmonella reptile strains, in line with a previous study conducted on species of gecko in Italy (10). This antibiotic is the most widely used in human medicine in Spain (76) and could thus be implicated in possible transmission of resistance from humans to reptiles, as a consequence of the direct and indirect contact between reptiles and their owners (75,77,78).…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, the level of resistance to NAL, CHL, SXT, TM, CAZ, CTX, and CIP in reptile Salmonella strains was relatively low. Resistance to CAZ contrasts with a survey conducted on geckos by Russo et al (10), who showed a high resistance of Salmonella species to this antimicrobial, that is used in reptiles to treat infections or prophylactically after a traumatic injury (79). Moreover, it is important to note that fluoroquinolones (e.g., CIP) are the drugs of choice for invasive salmonellosis infections in humans (adults) and cephalosporins (e.g., CTX and CAZ) in children (21), although both are implicated in a reduced effectiveness of Salmonella treatment (77).…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Concurrently, a national outbreak of L. monocytogenes foodborne illness associated with cantaloupes in humans occurred, although the bacterial strains were genetically distinct. The ability of foodborne pathogens to infect exotic pets is poorly investigated (Russo et al, ) and, although rare, should be considered, especially for sugar gliders whose diet consists of many exotic fruits often imported from other countries and subjected to handling and storage that could negatively affect their microbiological quality. Also, insects consumed in the sugar gliders’ diet may carry pathogens even at long distances from their origin and breeding sites.…”
Section: Resultsmentioning
confidence: 99%
“…were also detected in 3 of the 38 tortoises in a private breeding (3/38; 8%) and 15 turtles in the shelter (15/ 40; 37.5%) [63]. Also in Italy, Russo et al [67] evaluated Salmonella-prevalence in housed gecko. Faecal swabs were collected from 70 apparently healthy captive gecko and Salmonella spp.…”
Section: Salmonella Spp Prevalence In Amphibians and Reptilesmentioning
confidence: 99%